2021
DOI: 10.1101/2021.09.23.461492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic behavior analysis for phytochemical traits in coriander: Heterosis, inbreeding depression and genetic effects

Abstract: Increasing fruit yield, fatty acids and essential oils content in coriander are the main objectives. Reaching them need to understand the nature of gene action and quantifying the heterosis and inbreeding depression. Six genetically diverse parents, their 15 F 1 one-way hybrids and 15 F 2 populations were evaluated under different levels of water treatments. Beside the water treatment and genotype effects, the genetic effects of general (GCA) and specific (SCA) combining ability and their interactions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…As to the future study of depression, recent research on depressive disorders has sparked hopes of significant progress against these age-old problems. By the rapidly developing Genetic technology, the complex interactions between our DNA and the environment in producing depression are on the right way to be revealed (Gholizadeh & Khodadadi, 2021). The Neuroimaging studies showed in Fig.…”
Section: Medicationsmentioning
confidence: 99%
“…As to the future study of depression, recent research on depressive disorders has sparked hopes of significant progress against these age-old problems. By the rapidly developing Genetic technology, the complex interactions between our DNA and the environment in producing depression are on the right way to be revealed (Gholizadeh & Khodadadi, 2021). The Neuroimaging studies showed in Fig.…”
Section: Medicationsmentioning
confidence: 99%